The shape of the heart - Vinken, P. J. (Pierre Jacques), 1927-2011; Mason, Peter, 1952- (Amsterdam : Elsevier, 2000)
Why is the heart not heart-shaped? The scalloped heart. Rough chronology. The heart as a cave - Hendrik Spiegel's Antrum platonicum. Appendices. Notes. References.
Why is the shape of a popular icon like the heart at variance with it's true form? A heart has neither a dent nor fold in its base, it is not 'nipped in the waist' and it does not have a sharp point on its underside. This work also contains a section devoted to a cave, shaped like the interior of the heart.
Keywords: Anatomy -- Macroscopic, incl comparative; Heart -- Anatomy; Heart -- Symbolic aspects; History of medicine -- Netherlands; Internal medicine -- Cardiology; Medicine and arts